EVALUASI KAPABILITAS PENGGUNAAN SISTEM POS DI LAFERA SPACE BERDASARKAN FRAMEWORK COBIT 2019: EVALUATION OF POS SYSTEM USAGE CAPABILITY AT LAFERA SPACE BASED ON THE COBIT 2019 FRAMEWORK - Kurniawan, Kia; Media, Dirga; Haryadi, Yogi; Megawati (STIKOM Uyelindo Kupang, 2026)
Sistem Point of Sale (POS) telah menjadi komponen penting dalam operasional bisnis ritel dan kuliner, termasuk pada usaha mikro seperti Lafera Space. Namun, pemanfaatan sistem POS masih belum optimal. Penelitian ini bertujuan mengevaluasi tingkat kapabilitas pengelolaan sistem POS di Lafera Space dengan menggunakan framework COBIT 2019 pada tiga domain: APO04 (Manage Innovation), BAI02 (Manage Requirements Definition), dan MEA01 (Monitor, Evaluate and Assess Performance and Conformance). Metode penelitian meliputi observasi, wawancara, serta penyebaran kuesioner berbasis atribut proses COBIT 2019. Hasil evaluasi menunjukkan bahwa ketiga domain berada pada capability level 1 hingga 2. Rekomendasi strategis diajukan untuk mengatasi kesenjangan dan meningkatkan tata kelola sistem POS secara berkelanjutan. Point of Sale (POS) systems have become an important component in retail and culinary business operations, including micro businesses such as Lafera Space. However, the utilization of POS systems is still not optimal. This study aims to evaluate the level of POS system management capabilities at Lafera Space using the COBIT 2019 framework in three domains: APO04 (Manage Innovation), BAI02 (Manage Requirements Definition), and MEA01 (Monitor, Evaluate, and Assess Performance and Conformance). The research methods include observation, interviews, and the distribution of a questionnaire based on the COBIT 2019 process attributes. The evaluation results indicate that all three domains are at capability levels 1 to 2. Strategic recommendations are proposed to address the gaps and improve the management of the POS system sustainably.